Footbath Therapy in Stroke Rehabilitation: A Systematic Review of Physical and Psychological Outcomes and Implication for Nursing Practice - Eni Marwanti; I Made Kariasa; Riri Maria (Universitas Muhammadiyah Semarang, 2026)
Stroke remains a major neurological condition that frequently results in long-term functional impairments and reduced quality of life among survivors. In addition to pharmacological therapy, various non-pharmacological interventions have been investigated to support recovery, among which footbath therapy has demonstrated potential benefits for both physical and psychological outcomes. This systematic review aimed to identify and synthesise current scientific evidence regarding the effectiveness of footbath therapy in stroke patients. Following PRISMA guidelines, a comprehensive search was conducted for articles published between 2014 and 2024 in ProQuest, ScienceDirect, Cochrane, EBSCO, PubMed, and Google Scholar, using keywords developed through the PICO framework. A narrative synthesis approach was employed to analyze the findings, with six eligible studies comprising four randomized controlled trials (RCTs) and two quasi-experimental studies. The findings suggest that footbath therapy may enhance parasympathetic nervous system activity, improve muscle strength, and reduce spasticity and physical fatigue. Psychologically, it appears to alleviate anxiety and psycho-emotional stress while promoting comfort and sleep satisfaction. The evidence suggests potential benefits of footbath therapy in stroke patients. Given its low risk and ease of implementation, footbath therapy may be regarded as a promising complementary intervention in stroke patients. However, the evidence is based on a small number of heterogeneous studies, and the overall quality of evidence appears limited, suggesting that the findings should be interpreted with caution. Therefore, high-quality randomized controlled trials are needed to strengthen the evidence.